Arany János születésének 100. évfordulója és a háború a nagyszalontai Emlékegyesület értesítése a Debreceni m. kir. Tudományegyetemnek az ünnepség elmaradásáról - Király, Sándor (Gerundium, 2018)
the Centenary of the Birth of János Arany and the War. The Message of the Memorial Society from Nagyszalonta to the University of Debrecen about the Cancellation of the Ceremony. One hundred years ago and one hundred years after the birth of Arany the memorial society prepared for a nationwide celebration in Nagyszalonta. They sent their official invitation to every literary and scholarly society, with the University of Debrecen among them. Nándor Láng, who was the Rector of the university in the 1916/17. academic year gave the mandate to Károly Pap to attend the ceremony and represent the university. Károly Pap, who was the dean of the faculty of arts, accepted this with pleasure because he was a researcher of the poetry of Arany. But the ceremony was postponed because the train service became unreliable due to the war. The nationwide ceremony had to be cancelled because of the bad traffic conditions and it was never held in Nagyszalonta in 1917. This printed media sources inform us about this and the effect of the Great War on the centenary of the birth of János Arany.